2014
DOI: 10.1371/journal.pone.0084995
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Xanthomonas translucens Pathogenic on Wheat and Barley Reveals Cross-Kingdom Gene Transfer Events and Diverse Protein Delivery Systems

Abstract: In comparison to dicot-infecting bacteria, only limited numbers of genome sequences are available for monocot-infecting and in particular cereal-infecting bacteria. Herein we report the characterisation and genome sequence of Xanthomonas translucens isolate DAR61454 pathogenic on wheat and barley. Based on phylogenetic analysis of the ATP synthase beta subunit (atpD) gene, DAR61454 is most closely related to other X. translucens strains and the sugarcane- and banana- infecting Xanthomonas strains, but shares a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 48 publications
1
30
0
1
Order By: Relevance
“…Xanthomonas translucens is a pathogen of wheat and/or barley (Adhikari et al, 2011) causing bacterial leaf streak (BLS), or 'black chaff', which is a significant wheat disease globally with up to 40 % yield losses (Forster and Schaad, 1988). Current understanding of cereal-bacterial pathogen interactions is limited (Gardiner et al 2014) and a brachypodium-X. translucens model system may help to improve such understanding.…”
Section: Bacterial Leaf Streak (Xanthomonas Translucens)mentioning
confidence: 99%
See 2 more Smart Citations
“…Xanthomonas translucens is a pathogen of wheat and/or barley (Adhikari et al, 2011) causing bacterial leaf streak (BLS), or 'black chaff', which is a significant wheat disease globally with up to 40 % yield losses (Forster and Schaad, 1988). Current understanding of cereal-bacterial pathogen interactions is limited (Gardiner et al 2014) and a brachypodium-X. translucens model system may help to improve such understanding.…”
Section: Bacterial Leaf Streak (Xanthomonas Translucens)mentioning
confidence: 99%
“…Recently, the genome of a wheat and barley-infecting X. translucens isolate 'DAR61454' has been sequenced (Gardiner et al, 2014). We have observed that DAR61454 is pathogenic on a range of brachypodium ecotypes, including major community ecotypes Bd21-3 and Bd21 (Fig.…”
Section: Bacterial Leaf Streak (Xanthomonas Translucens)mentioning
confidence: 99%
See 1 more Smart Citation
“…Other genome-scale reconstructions are available for maize [239] and barley [240], a host of X. translucens pv. translucens [241,242], and it is likely that more plant models will become available with the increasing number of genomes being sequenced. On the pathogen side, besides the Xcc models mentioned above, there are genome-scale metabolic reconstructions for other plant pathogenic bacteria [243][244][245].…”
Section: Environmental Systems Biology As a Perspective For Analysis mentioning
confidence: 99%
“…O trabalho clássico de Singh (1986) e outros mais recentes (ARSHIYA et al, 2014;GARDINER et al, 2014;MISHRA et al, 2013;TARDIANI et al, 2014) Mishra et al (2013) identificaram 10 genes (Xa1, Xa3, Xa4, Xa5, Xa7, Xa8, Xa10, Xa11, Xa13, Xa21) …”
Section: Diversidade Genética De Xanthomonasunclassified